Implementasi Pendekatan Pembelajaran Inovatif Dalam Meningkatkan Motivasi Belajar Dan Partisipasi Aktif Siswa Pada Proses Pembelajaran - Salwa Khairunnisa; Dwi Ajeng Maulidya Makalao (STIT Fatahillah, 2026)
This study aims to describe the implementation of innovative learning approaches in improving students' learning motivation and active participation in the learning process at SMAN 1 Darangdan. The background of this study is based on the fact that there are still students who are less active in learning activities and whose learning motivation is not evenly distributed in the classroom. Innovative learning approaches are considered as an effort to create a more active, creative, and enjoyable learning atmosphere. This study used a qualitative approach with a descriptive method. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects consisted of teachers and students at SMAN 1 Darangdan. The results showed that the implementation of innovative learning approaches through group discussions, problem based learning, collaborative learning, presentations, and the use of digital media was able to increase students’ enthusiasm for learning. Students became more active in asking questions, expressing opinions, collaborating, and participating in the learning process. In addition, students’ learning motivation also increased because learning became more interesting and less monotonous. However, there were still several obstacles, such as limited time, differences in students’ abilities, and inadequate supporting facilities. The conclusion of this study indicates that innovative learning approaches play an important role in improving students’ learning motivation and active participation, as well as supporting the creation of an effective learning process.